THE INFLUENCE OF SUSTAINABILITY IMPLEMENTATION (PROFIT, PEOPLE, PLANET) ON FINANCIAL PERFORMANCE OF COMPANIES IN SRI-KEHATI INDEX - Uriel Kafka Lungguran; Sumani Sumani (Jurnal Akuntansi, 2022)
Triple bottom line is a framework concept that take notice to economic performance which can be seen on profitability, social care performance, and empowerment of environmental biodiversity performance. The purpose of this research is to examine and explain the effect of 3P (profit, people, planet) on abnormal return.This research uses secondary data which is obtained from Indonesian Stock Exchange (IDX). The population of this research can be counted 25 companies that listed in SRI-KEHATI Index on 2016-2019 period and were taken 17 companies that fulfill the criteria. With the result that the sample of this research can be counted 64 data. The research method uses descriptive statistic analysis, classic assumption test, and multiple linear regression by using Statistic Package for Social Science (IBM SPSS Statistic 25th version) to proceed data.The research result indicates that there is a significant with negative effect on planet variable as independent variable on abnormal return as dependent variable. Furthermore, there is no significance indicate by profit variable and people variable as independent variable on abnormal return as dependent variable.